Recurrent chronic subdural hematoma: Report of 13 cases - Haciyakupoglu, Ersin; Yilmaz, Dervis Mansuri; Kinali, Burak; Arpaci, Taner; Akbas, Tugana; Haciyakupoglu, Sebahattin (DE GRUYTER POLAND SP ZOO, 2018)
Chronic subdural hematoma is a frequent type of hemorrhage, which terminates with mortality if not diagnosed and treated early. The aim of this clinical study is to evaluate the patients with unilateral and bilateral recurrent chronic subdural hematoma. The study group consisted of 13 cases with unilateral and bilateral recurrent chronic subdural hematomas who underwent aggressive wide craniotomy, duraectomy, inner and outer membranectomy, dural border coagulation, incision through cortical vein trace and hang up of dural edge, between 2009 - 2016. All of our patients were diagnosed by preoperative Magnetic Resonance Imaging. We evaluated the age, gender, complaints and neurologic signs, localization and thickness of the hematoma. We can estimate that wide craniotomy, duraectomy and membranectomy is a good option in preventing recurrent chronic subdural hematoma and complications.
Keywords: Recurrent; Chronic subdural hematoma; Craniotomy; Duraectomy; Membranectomy; Surgical treatment